Re-sequenciamento de Corynebacterium pseudotuberculosis e a busca por mecanismos de tropismo pelo hospedeiro - Enrico Giovanelli Tacconi Gimenez (2023)
Corynebacterium pseudotuberculosis is the causative agent of caseous lymphadenitis (CLA) in several animals, including camelids, ruminants, horses and humans. CLA can result in severe economic losses, especially in camelids, which are highly valued as companion animals. Little is known about the mechanisms involved in tropism for different hosts. Cp162 strain isolated from camel is the only one of this host that had its genome sequenced. This study aimed to evaluate the evolution of genome assemblies of the Cp162 lineage, identify possible genes related to host tropism and understand the genomic diversity of C. pseudotuberculosis through comparative genomics and phylogeny analyses. Since the first assembly, there was an increase of 88 kb, 121 protein coding genes, a reduction in the number of pseudogenes and correction of two inversions and one rearrangement. Compared to 129 other genomes of the species, Cp162 has four unique genes, which encode two transposases and two truncated genes. Three genes uniquely missing from this lineage are lysG and two that encode “NUDIX domain protein”, and a hypothetical protein. No genes could be associated with the camel host tropism, which suggests that the tropism could be associated with sequence polymorphisms rather than the presence and absence of genes, and more genomes from this host need to be analyzed. The analysis showed that the C. pseudotuberculosis pangenome is closed, but there are many unknown genes in this genome that may be associated with tropism for other hosts.